The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1002/chem.200701818
|View full text |Cite
|
Sign up to set email alerts
|

TEMPO/HCl/NaNO2 Catalyst: A Transition‐Metal‐Free Approach to Efficient Aerobic Oxidation of Alcohols to Aldehydes and Ketones Under Mild Conditions

Abstract: Hydrochloric acid, a very inexpensive and readily available inorganic acid, has been found to cooperate exquisitely with NaNO(2)/TEMPO in catalyzing the molecular-oxygen-driven oxidation of a broad range of alcohol substrates to the corresponding aldehydes and ketones. This transition-metal-free catalytic oxidative conversion is novel and represents an interesting alternative route to the corresponding carbonyl compounds to the metal-catalyzed aerobic oxidation of alcohols. The reaction is highly selective wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
74
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 186 publications
(78 citation statements)
references
References 119 publications
1
74
0
1
Order By: Relevance
“…This is probably because NaNO 2 would decompose into NO and NO 2 under the acidic conditions, and be lost at the stage of product separation. [6,7,8] In this regard, NaNO 2 was replenished for the subsequent run. The results showed that the yield and selectivity of the products just had a slight decrease after the fourth run (entries 4-6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is probably because NaNO 2 would decompose into NO and NO 2 under the acidic conditions, and be lost at the stage of product separation. [6,7,8] In this regard, NaNO 2 was replenished for the subsequent run. The results showed that the yield and selectivity of the products just had a slight decrease after the fourth run (entries 4-6).…”
Section: Resultsmentioning
confidence: 99%
“…In this context, Liang and Hu et al made a great breakthrough in this field. At first, they developed threecomponent catalyst systems, including TEMPO/Br 2 / NaNO 2 , [6] TEMPO/1,3-dibromo-5,5-dimethylhydantoin/NaNO 2 , [7] TEMPO/HCl/NaNO 2 , [8] TEMPO/HBr/ tert-butyl nitrite (TBN), [9] which would be considered to go through a sequential tricycle with a two-electron transfer mechanism. Then, a TEMPO/TBN doublecomponent and sequential bicycle catalyst system was successfully exploited for alcohol oxidations, and even has been applicable to substrates containing acid-sen-sitive functional groups without the need of the toxic halogen source and acid.…”
Section: Introductionmentioning
confidence: 99%
“…1], has been extensively used as a catalyst for the oxidation of alcohols in a wide range of chemistry. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] In particular, TEMPO-catalyzed alcohol oxidation has high priority in the pharmaceutical industry as an efficient, mild, and environmentally acceptable method. However, TEMPO is often inefficient in the oxidation of structurally hindered alcohols, posing a problem in the oxidation of secondary alcohols.…”
mentioning
confidence: 99%
“…We next examined the aerobic oxidation conditions [6][7][8][14][15][16][17][18][19] using the nitroxyl radical/NaNO 2 /Air/AcOH system, 29) which we have recently reported as versatile transition-metal-free and halogen-free conditions.…”
mentioning
confidence: 99%
“…Subsequent optimization of our initial catalytic system led to an improved and greener protocol, whereby primary alcohols were selectively oxidized to the corresponding aldehydes in high yields using HCl in place of molecular bromine, but the optimized system required a high TEMPO loading to accomplish the oxidation. [9] On the other hand, the transition metal-catalyzed aerobic oxidation of alcohols has been a field of intensive research due to the inherent advantages of transition metals in dioxygen activation. Therefore, we are also interested in the discovery and development of an innovative transition metal catalyst system for the aerobic oxidation of alcohols, especially for oxidative conversion of primary alcohols to aldehydes.…”
mentioning
confidence: 99%